The effect of classroom lectures and a movie recommendation on pharmacy students' attitudes and social distancing toward people with schizophrenia - Deborah Oyine Aluh, MPharm; Kosisochi Chinwendu Amorha, PhD, FPCPharm; Temitayo Adeola Anthony-Awi (American Association of Psychiatric Pharmacists, 2022)
Introduction: Stigma and negative attitudes toward people with mental health disorders can impair the provision of pharmaceutical care. The purpose of the study was to assess the effect of classroom lectures on mental health disorders and a movie recommendation on pharmacy students' attitudes and stigma toward persons with schizophrenia (PwS). Methods: The study consisted of a presurvey and postsurvey carried out among final-year pharmacy students of the University of Nigeria Nsukka. A survey comprising 3 sections on sociodemographic details, attitudes toward PwS, and a social distance scale was given to conveniently sampled students before and after lectures on schizophrenia. Students were encouraged to watch a movie about the experiences of a PwS after the first lecture. Results: One hundred seventy-nine students (of the 200 sampled, response rate 91.1%) agreed to participate and completed the survey instrument before the clinical lecture, whereas 108 students who took part in the presurvey participated in the postsurvey (response rate of 76.0%). The overall mean negative attitude score reduced from 2.79±0.412 to 2.72±0.357. The overall mean social distance score increased from 2.48±0.415 to 2.49±0.467, indicating increased stigma. In both presurveys and postsurveys, people with a friend or relative with schizophrenia had a lower mean negative attitude score compared with those who did not. People who had watched the movie recommendation (n = 85) had a higher mean negative attitude (2.74 vs 2.67, P =.433) and a lower social distance toward PwS (2.57 vs 2.48, P =.415). Discussion: Classroom lectures on mental health among pharmacy students might not significantly improve the overall attitudes and social distance toward PwS. Schools of pharmacy should consider alternative formats of teaching mental health-related topics, such as contact with real patients and simulation.